Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5301/tj.5000574
|View full text |Cite
|
Sign up to set email alerts
|

The ATS/ERS/JRS/ALAT Statement “IPF by HRCT” could Predict Acute Exacerbation of Interstitial Lung Disease in Non-small Cell Lung Cancer

Abstract: ILD with a UIP pattern or possible UIP pattern by the classification could be a risk factor for AE-ILD in NSCLC patients with ILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Preexisting ILD was the consistent risk factor for developing fibrosis in our study, as was found in previous reports . Specifically, the UIP pattern or a possible UIP pattern visible in the CT scan was proven to be the prognostic factor for developing severe CIP or acute exacerbation of ILD . We found that moderate to severe emphysema also increased the risk of developing fibrosis and severe fibrosis over 11% in extent as well.…”
Section: Discussionsupporting
confidence: 89%
“…Preexisting ILD was the consistent risk factor for developing fibrosis in our study, as was found in previous reports . Specifically, the UIP pattern or a possible UIP pattern visible in the CT scan was proven to be the prognostic factor for developing severe CIP or acute exacerbation of ILD . We found that moderate to severe emphysema also increased the risk of developing fibrosis and severe fibrosis over 11% in extent as well.…”
Section: Discussionsupporting
confidence: 89%
“…Although chemotherapy is often used for patients with NSCLC and ILD, evidence for improved prognosis with chemotherapy is lacking. Several studies found that the incidence rate of acute exacerbation (AE) of ILD ranged between 5% and 35% in patients with NSCLC and ILD undergoing chemotherapy . We recently reported that mortality after AE in these patients was 20% .…”
Section: Introductionmentioning
confidence: 99%
“…A UIP pattern on CT was reported to be a risk factor for chemotherapy-induced acute exacerbation of ILD (1,11,14). Another report demonstrated that lower forced vital capacity is a risk factor, but a UIP pattern is not (4).…”
Section: Discussionmentioning
confidence: 99%